2008
DOI: 10.1128/mcb.02011-07
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of RASSF1A/MOAP-1 Association with Death Receptors

Abstract: RASSF1A is a tumor suppressor protein involved in death receptor-dependent apoptosis utilizing the Bax-interacting protein MOAP-1 (previously referred to as MAP-1). However, the dynamics of death receptor recruitment of RASSF1A and MOAP-1 are still not understood. We have now detailed recruitment to death receptors (tumor necrosis factor receptor 1 [TNF-R1] and TRAIL-R1/DR4) and identified domains of RASSF1A and MOAP-1 that are required for death receptor interaction. Upon TNF-␣ stimulation, the C-terminal reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
119
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(121 citation statements)
references
References 54 publications
1
119
0
1
Order By: Relevance
“…Detailed five-amino acid deletions revealed that the sequences 131 SQAEI and 300 ELHNFL were required for microtubule localization ( Figure 1b). It is interesting that 131 SQAEI is the ataxia telangeictasia mutated (ATM) phosphorylation site on RASSF1A (Agathanggelou et al, 2001) and 300 ELHNFL is just downstream of the site of association with the only known downstream effector of RASSF1A-mediated cell death, the modulator of apoptosis 1 (MOAP-1 at amino acid 311 REEEEHL) (Baksh et al, 2005;Foley et al, 2008). These results are similar to some of the published observations, which suggest that both N-and C-terminal regions of RASSF1A determine microtubule localization.…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…Detailed five-amino acid deletions revealed that the sequences 131 SQAEI and 300 ELHNFL were required for microtubule localization ( Figure 1b). It is interesting that 131 SQAEI is the ataxia telangeictasia mutated (ATM) phosphorylation site on RASSF1A (Agathanggelou et al, 2001) and 300 ELHNFL is just downstream of the site of association with the only known downstream effector of RASSF1A-mediated cell death, the modulator of apoptosis 1 (MOAP-1 at amino acid 311 REEEEHL) (Baksh et al, 2005;Foley et al, 2008). These results are similar to some of the published observations, which suggest that both N-and C-terminal regions of RASSF1A determine microtubule localization.…”
Section: Resultssupporting
confidence: 78%
“…Similarly, RASSF1A self association was preserved in the dMT mutant of RASSF1A in a similar way to wild-type self association ( Figure 4a). This self association is required before RASSF1A recruitment to death receptors (Foley et al, 2008). These data suggest that the dMT mutant of RASSF1A still maintained a tertiary structure to allow both self and MOAP-1 association, but not death receptor association.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations